Electric vehicle smart charging coordination on a residential distribution grid / Norhasniza Md Razali, Hasmaini Mohamad and Zaipatimah Ali - Md Razali, Norhasniza; Mohamad, Hasmaini; Ali, Zaipatimah (UiTM Press, 2023)
The future grid with high plug-in electric vehicles (PEVs) penetration poses great challenges to the stability of the distribution system. Power quality degradation and transformer overload are some of the critical issues that need to be addressed. To alleviate the effect, smart charging coordination has been introduced using various optimization techniques and considerations on PEV penetration, charging parameters as well as grid operation limits. This study presents smart charging coordination of PEVs in a residential distribution network considering a daily residential load demand profile in Malaysia using a particle swarm optimization (PSO) algorithm. The proposed optimization is operated within several operating constraints such as power demand and bus voltage constraints while achieving the objective function of load optimization and minimum power loss. The performance of the proposed method is evaluated using a 415V IEEE 33-bus radial distribution network system with each bus connected to a residential feeder populated with PEVs. Results are compared between uncoordinated and coordinated charging considering four different PEV penetration levels. The proposed coordinated charging manages to optimize the load with PEV charging and gives a promising reduction in the network’s power losses compared to uncoordinated charging.